DAMAI Model: A Conflict Resolution towards Peaceful Indonesia - LABOBAR, Kresbinol; DARMAWAN, I Putu Ayub (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
In the Unitary State of the Republic of Indonesia, a harmonious relationship between practitioners of various faiths is seen as one of the most desired prerequisites, making it a continuing topic of debate. Tensions, disputes, and even acts of violence between members of different faiths are not caused by chance but rather by the adherents’ particular religious beliefs-inspired manner of life. By analysing the theological models established by Christian theologians of recent centuries, the authors gave their view on the problem’s origins, namely the influence of using specific theological models on other faiths. Currently, exclusivism, inclusivism, and pluralism are the most prevalent theological frameworks used by each religion to create and propagate its ideas. Using these models leads religious devotees to lose their impartiality while examining other faiths, resulting in a distorted viewpoint. To foster a climate of mutual respect among members of diverse faiths, the authors propose DAMAI, an alternative model of a theological approach to many religions that consists of Dialogue (Dialog), Justice (Adil), Charity (Mengasihi), Security (Aman), and Innovation (Inovasi). This concept benefits from becoming a tool for dispute resolution and fostering a religious lifestyle defined by tolerance and respect among members of different faiths.